Superword: A honeyword system for achieving higher security goals. Issue 103 (April 2021) - Guo, Yimin; Zhang, Zhenfeng; Guo, Yajun
Abstract: Generating honeywords for each user's account is an effective way to detect whether password databases are compromised. However, there are several underlying security issues associated with honeyword techniques that need to be addressed, for example, (1) How to make it more difficult for an attacker to find an accurate match of "username-real password"? (2) How to prevent the intersection attack in multiple systems caused by password reuse without reducing usability? (3) How to reduce the success rate of targeted password guessing? In this study, we first propose a "matching attack" model and find that although Erguler's honeyword system can achieve perfect flatness, the success rate of the attacker is 100% under matching attack. Secondly, we propose a new honeyword approach named Superword that isolates the direct relationship between username and the corresponding hashed password in password files. Additional honeypots are mixed with real accounts to detect online guessing attacks. The analysis reveals that our approach makes a matching attacker difficult to find a real password from N password hashes. Since there is no connection between the username and password in password files, our honeyword system also alleviates the multiple systems intersection attack and targeted password guessing.